Polymorphic analysis of field collected aedes albopictus from Subang Bestari, Shah Alam based on internal transcribed spacer 2 (ITS2) marker / Wan Zainab Wan Othman - Wan Othman, Wan Zainab (2015)
The dramatic worldwide expansion of Aedes albopictus and its vector competence for numerous arboviruses especially dengue viruses (DENV) represent a growing threat to public health security. Being a secondary vector of DENV, the studies of Aedes albopictus is less focused unlike Aedes aegypti. The prospect of worldwide polymorphism of Aedes albopictus prompted the development of rapid, polymerase chain reaction (PCR)-based method and phylogenetic analysis on internal transcribed spacer 2 (ITS2) marker for evaluating the intrapopulation diversity of this species. ITS2 region was amplified from five singles and one pooled specimens of Aedes albopictus collected from Subang Bestari, Shah Alam (SB) along with the lab strain (LS) that act as a positive control and phylogenetic analysis was conducted on them. The obtained result revealed a PCR product of 337bp product. Based on phylogenetic analysis, SB and LS samples were in different clusters to each other including pooled samples. However, they showed a strong ancestral relationship to other global population mostly to the Italy population and highly similar to Mayotte population. The ITS2 marker here implemented revealed the distribution of genetic diversity within and between populations and provides clues on the dispersion dynamics of this species. It appears that the diffusion of this species to global may due to the migration aspect and it may survive in subtropical environments. The ITS2 marker is thus an important tool for future phylogeographical studies in Malaysia.